Transformasi Digital Arsip Rumah Sakit Daerah Menuju Paperless Office - Muhammad Alfi Alfarizi; Muhammad Aditya Rachman; Erni Erdita (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Digital transformation in archives management at Regional General Hospitals (RSUD) is a crucial step in supporting government policies regarding electronic-based government systems and improving the quality of healthcare services. This study aims to analyze the transition process from a conventional paper-based archiving system to a paperless office ecosystem. The main focus of the study includes information technology infrastructure readiness, human resource (HR) competency in operating the hospital information system (SIMRS), and managerial obstacles encountered during the digitalization process. The methodology used is descriptive qualitative, with data collection techniques through field observations and current literature reviews. The results show that implementing digital archives significantly reduces medical record retrieval time by up to 70%, minimizes the risk of damage to physical documents due to environmental factors, and optimizes physical storage space in the hospital. However, major challenges lie in standardizing data security (cybersecurity) and data integration between service units. The study concludes that successfully moving towards a paperless office requires synergy between appropriate technology investments, strong internal regulations, and an organizational culture that adapts to digital change.